CHALLENGES AND PROSPECTS IN TEACHING THE UZBEK LANGUAGE TO FOREIGN STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the current challenges and future prospects in teaching the Uzbek language to foreign students, with a focus on the higher education context in Uzbekistan. The growing interest in Uzbek as a foreign language, driven by increased international mobility and Uzbekistan’s expanding diplomatic, cultural, and economic presence, necessitates a reevaluation of pedagogical approaches and curriculum development. The study examines issues such as the lack of standardized teaching materials, limited teacher training in the methodology of teaching Uzbek as a foreign language, and the influence of students’ native language backgrounds. At the same time, it highlights promising developments such as the integration of digital technologies, the emergence of research-based instruction models, and the potential of international academic collaboration. Drawing on both qualitative and comparative analysis, the article offers a critical assessment of current practices and outlines directions for innovation and reform.